2007
DOI: 10.4049/jimmunol.179.3.1768
|View full text |Cite
|
Sign up to set email alerts
|

The Related Adaptors, Adaptor in Lymphocytes of Unknown Function X and Rlk/Itk-Binding Protein, Have Nonredundant Functions in Lymphocytes

Abstract: Adaptors play a critical role in regulating signaling pathways that control lymphocyte development and activation. Adaptor in lymphocytes of unknown function X (ALX) and Rlk/Itk-binding protein (RIBP) are adaptors related by structure and sequence, coexpressed in T cells. Mice deficient for each adaptor demonstrated that ALX and RIBP, respectively, negatively and positively regulate T cell activation in response to TCR/CD28 stimulation. However, these results did not preclude that they may function redundantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…While Drappa and colleagues reported that injection of superantigen did not lead to deletion of the targeted T cells in SH2D2A -deficient mice [13], this was not confirmed by another group [12]. In a classic model of negative selection in the thymus, SH2D2A -deficient H-Y TCR-transgenic male mice displayed increased numbers of both DP and SP CD4+ and CD8+ thymocytes compared normal mice [12], suggesting that negative selection in the absence of SH2D2A is not as efficient as in wild type mice. In the normal situation, clonal deletion in the thymus occurs late in development, at the DP-to-SP transition [35].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While Drappa and colleagues reported that injection of superantigen did not lead to deletion of the targeted T cells in SH2D2A -deficient mice [13], this was not confirmed by another group [12]. In a classic model of negative selection in the thymus, SH2D2A -deficient H-Y TCR-transgenic male mice displayed increased numbers of both DP and SP CD4+ and CD8+ thymocytes compared normal mice [12], suggesting that negative selection in the absence of SH2D2A is not as efficient as in wild type mice. In the normal situation, clonal deletion in the thymus occurs late in development, at the DP-to-SP transition [35].…”
Section: Discussionmentioning
confidence: 92%
“…Despite its presumed role in regulating Lck and Itk during T cell signaling, SH2D2A -deficient mice develop normally and have a normal distribution of double negative (DN), double positive (DP) and single positive (SP) thymocytes [11], [12]. However, when stimulated with soluble anti-CD3 or anti-CD3/CD28 antibodies, peripheral T cells from SH2D2A -deficient mice proliferate less vigorously compared to cells from control mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in Notch target gene expression were also observed in the CD4 SP and CD8 SP populations as well (all but Dtx1 expression in CD8 SP T cells were statistically significant with at least p<0.01). RIBP expression, which remains constant throughout T cell development was examined as a control (Perchonock et al, 2007). Deletion of NKAP did not alter RIBP expression in DP, CD4 SP or CD8 SP populations, demonstrating that loss of NKAP does not generally increase transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of thymocyte development and T cell subpopulations were performed as previously described (24). Briefly, thymocyte single-cell suspensions were generated using 100-m-pore-size nylon mesh filters (BD Biosciences) and surface stained with the following reagents: fluorescein isothiocyanate (FITC)-CD8, TCR␤, TCR␥␦, CD3ε, B220, CD19, CD11c, DX5, NK1.1, Ter119, Mac1 (BD Pharmingen), phycoerythrin (PE)-TCR␤, CD8, CD3ε PerCP-CD4, allophycocyanin (APC)-CD8, CD25, and APC-Cy7-c-kit (eBioscience).…”
mentioning
confidence: 99%